Lidské embryonální renální multipotentní progenitory mohou přispět k regeneraci u akutního selhání ledvin - Lazzeri, E; Crescioli, C; Ronconi, E (Postgraduální nefrologie, 2007)
Bone marrow-and adult kidney-derived stem/progenitor cells hold promise in the development of therapies for renal failure. Here is reported the identification and characterization of renal multipotent progenitors in human embryonic kidneys that share CD24 and CD133 surface expression with adult renal progenitors and have the capacity for self-renewal and multilineage differentiation. It was found that these CD24+CD133+ cells constitute the early primordial nephron but progressively disappear during nephron development until they become selectively localized to the urinary pole of Bowman's capsule. When isolated and injected into SCID mice with acute renal failure from glycerol-induced rhabdomyolysis, these cells regenerated different portions of the nephron, reduced tissue necrosis and fibrosis, and significantly improved renal function. No tumorigenic potential was observed. It is concluded that CD24+CD133+ cells represent a subset of multipotent embryonic progenitors that persist in human kidneys from early stages of nephrogenesis. The ability of these cells to repair renal damage, together with their apparent lack of tumorigenicity, suggests their potential in the treatment of renal failure.
Keywords: Antigens, CD; renální insuficience; Kidney Tubules; CD antigeny; Humans; ledvinové kanálky; Microscopy, Confocal; Nephrons; myši SCID; antigen CD24; Mice, SCID; konfokální mikroskopie; lidé; zvířata; myši; peptidy; Mice; Peptides; CD24 Antigen; Stem Cells; glykoproteiny; Renal Insufficiency; Glycoproteins; embryo savčí; regenerace; rhabdomyolýza; kmenové buňky; Animals; Acute Disease; Rhabdomyolysis; nefrony; akutní nemoc; Regeneration; Embryo, Mammalian